A long goodbye the Soviet withdrawal from Afghanistan - Kalinovsky, Artemy M. (Harvard University Press, 2011)
Why did the USSR linger so long in Afghanistan? What makes this account of the Soviet-Afghan conflict both timely and important is its focus on the factors that prevented the Soviet leadership from ending a demoralizing and costly war and on the long-term consequences for the Soviet Union and the region
Keywords: Geschichte 1979-1989; Disengagement (Military science) / Case studies; HISTORY / Asia / Central Asia; HISTORY / Asia / General; HISTORY / Modern / 20th Century; Geschichte Asiens; Afghanistan-Konflikt -- 1979-1989; Rückzug; Asien; Afghanistan; Sowjetunion; Fallstudiensammlung